2006
DOI: 10.1113/jphysiol.2006.118281
|View full text |Cite
|
Sign up to set email alerts
|

The glutamate transporter EAAT5 works as a presynaptic receptor in mouse rod bipolar cells

Abstract: Membrane neurotransmitter transporters control the concentration of their substrate in the synaptic clefts, through the thermodynamic coupling of uptake to the movement of Na + and other ions. In addition, excitatory amino acid transporters (EAAT) have a Cl − conductance which is gated by the joint binding of Na + and glutamate, but thermodynamically uncoupled to the flux of glutamate. This conductance is particularly large in the retina-specific EAAT5 isoform. In the mouse retina, we located EAAT5 in both con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 52 publications
(79 reference statements)
8
101
1
Order By: Relevance
“…This suggests that GluNRs could be involved in modulatory regulation of the electrical synapses and that extrasynaptic receptors could be activated by spillover of glutamate escaping from the synaptic cleft after release from bipolar cells. Veruki et al (2006) found evidence for spillover of glutamate between neighboring rod bipolar cells and that ambient and transiently released glutamate can activate a glutamate transporter on rod bipolar axon terminals (see also Wersinger et al, 2006). This could imply that ambient levels of glutamate might be sufficient to activate GluNRs on AII amacrines and contribute to regulating the junctional conductance of their electrical synapses.…”
Section: Nmda Receptors In Aii Amacrine Cellsmentioning
confidence: 94%
“…This suggests that GluNRs could be involved in modulatory regulation of the electrical synapses and that extrasynaptic receptors could be activated by spillover of glutamate escaping from the synaptic cleft after release from bipolar cells. Veruki et al (2006) found evidence for spillover of glutamate between neighboring rod bipolar cells and that ambient and transiently released glutamate can activate a glutamate transporter on rod bipolar axon terminals (see also Wersinger et al, 2006). This could imply that ambient levels of glutamate might be sufficient to activate GluNRs on AII amacrines and contribute to regulating the junctional conductance of their electrical synapses.…”
Section: Nmda Receptors In Aii Amacrine Cellsmentioning
confidence: 94%
“…Bistratified bipolar cells make excitatory contacts to DA cells in cat and monkey retinas (Hokoc and Mariani, 1987;Kolb et al, 1990), and in fish retinas, bistratified bipolar cells exhibit L-AP-4-resistant ON light responses mediated by the glutamate-chloride cotransporter EAAT5 (Wong et al, 2005). However, in the mouse retina, EAAT5 localization and function differs from the fish because it is limited to rod, cone, and rod bipolar cell terminals, where it acts primarily to negatively regulate synaptic glutamate release and clear released glutamate (Hasegawa et al, 2006;Wersinger et al, 2006). Application of the transporter inhibitor TBOA causes loss of DA cell spontaneous activity as well as loss of both ON-transient and ON-sustained light responses, effects that are blocked by the glutamate receptor inhibitor CNQX (data not shown).…”
Section: Da Cell Light Responsesmentioning
confidence: 99%
“…On stepping the cell back to Ϫ60 mV, a relatively long-lasting tail current was observed. This tail-current involves several different response components, including a GABAergic component (Hartveit 1999;Singer and Diamond 2003) and a glutamate transporter-mediated component (Palmer et al 2003;Veruki et al 2006;Wersinger et al 2006). In addition, several discrete IPSCs were evoked (cf.…”
Section: Examples Of Whole Cell and Outside-out Patch Recordings Frommentioning
confidence: 99%